Child of the State, Mother of the Nation: Aboriginal Women and the Ideology of Motherhood - Fiske, Jo-Anne (Culture, 1993)
Around the world, in revolutions, periods of social reform, anti-colonial struggles and in international warfare, images of the mother have come to represent political aspirations. However common this phenomenon, is the meanings attributed to motherhood and the symbols employed to venerate it are constituted in the specificity of political struggles. In this paper I analyze the discourse of motherhood as constructed by aboriginal women of Canada in their struggle for self-determination and full citizenship in First Nations, looking at two discrete yet interrelated themes: the absence of patriarchal appropriation of motherhood symbols as found elsewhere among colonized peoples and the distinct development of motherhood symbols in women’s own political culture. By doing so, I hope to illuminate processes by which women produce moral accounts of themselves as mothers and in the process generate metaphors of motherhood that come to stand for aboriginal female identity. Finally, I conclude with an analysis of the failure of the motherhood discourse to alter First Nations’s women’s political subordination.